Arabic Language Learning in Non-Religious School Contexts: Analysis of Student Urgency and Learning Interest - Baihaki, Imam (At-Turost : Journal of Islamic Studies, 2024)
The purpose of this study was to explore the urgency of learning Arabic, identify factors influencing students' learning interest in non-religious schools, and analyze the relationship between learning urgency and student learning interest. Arabic has particular urgency in the context of Islam, but in this era of globalization, understanding Arabic provides a significant advantage in understanding the rich history, literature, and culture of Arabia. The research method used is a qualitative research method with a descriptive-analysis approach. The results showed that factors such as motivation, learning environment, and effective teaching influenced students' interest in Arabic. In addition, the urgency of learning Arabic is also positively related to students' interest in learning. Therefore, The urgency of learning Arabic is also positively related to students' interest in learning. Therefore, educators need to design more effective learning strategies to achieve the goals of religious education and Arabic language competence in non-religious school environments